The Effect of Celebrity Endorser, Convenience on Actual use Through Intentions on Tiktok Application Users - Marsuki, Marsuki; Hudayah, Syarifah; Zainurossalamia, Saida (Devotion : Journal of Research and Community Service, 2022)
The purpose of this study is to analyze and prove the influence of celebrity endorsers, convenience on actual use through intentions on tiktok application users in the city of Tenggarong. This study used 120 respondents and this study used a survey method with a sample in the city of Tenggarong with the Accidental Sampling Method sampling technique. Respondents were only interviewed once when they met. Data from the respondents were then tabulated and tested using statistical methods. Data were collected using a questionnaire research tool. Based on the results of the analysis and discussion, it can be concluded that convenience has a significant effect on the behavior of interest in Tiktok application users in the city of Tenggarong. So the first hypothesis is proven. Celebrity endorsers have a significant effect on the behavior of interest in Tiktok application users in the city of Tenggarong. So the second hypothesis is proven. Convenience has no significant effect on the actual use of Tiktok application users in the city of Tenggarong. So the third hypothesis is not proven. Celebrity endorsers have no significant effect on the actual use of Tiktok application users in the city of Tenggarong. So the fourth hypothesis is not proven. Interest behavior has a significant effect on the actual usage of Tiktok application users in the city of Tenggarong. So the fifth hypothesis is proven.